PDLLA/PRGD/β‐TCP conduits build the neurotrophin‐rich microenvironment suppressing the oxidative stress and promoting the sciatic nerve regeneration. Issue 10 (27th January 2014) - Qiu, Tong; Yin, Yixia; Li, Binbin; Xie, Lijuan; Yan, Qiongjiao; Dai, Honglian; Wang, Xinyu; Li, Shipu
Abstract A novel nerve guidance conduit comprising poly{(lactic acid)‐co‐[(glycolic acid)‐alt‐(l‐lysine)]} (PRGD), poly (d, l‐lactic acid) (PDLLA) and β‐tricalcium phosphate (β‐TCP) was constructed to facilitate the peripheral nerve regeneration. From the comparative study, PDLLA/PRGD/β‐TCP conduit achieved the best recovery in regard of the ultrastructure observation and the SFI evaluation. At the first stage of the injury (7 days), the maximum expression augments in ZnSOD (6.4 folds) and GPX4 (6.8 folds) were observed in PDLLA/PRGD/β‐TCP group; while striking rise in actin (6.8 folds), tubulin (5.6 folds), and ERM components expressions were observed later (35 days). Meanwhile, compared with PDLLA and PDLLA/PRGD conduits, PDLLA/PRGD/β‐TCP conduits achieved the highest local nerve growth factor (NGF) content and an accumulating BDNF content. We speculated that addition of RGD and β‐TCP in the composites were the main positive factors to build the microenvironment rich in NGF and BDNF, which help to counteract with the oxidative stress and to boost the cytoskeletal protein expressions. Therefore, PDLLA/PRGD/β‐TCP could be promising composites used in peripheral nerve regeneration. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 3734–3743, 2014.